A full scale experimental study of the structural behaviour of cold formed profiles with emphasis on the Zeta profile [microfiche] - Kemp, Leon (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1995.